Eating in a time of “crisis”: New health and dietary contexts in Spain. - Mabel Gracia-Arnaiz (Salud Pública de México, 2014)
This article analyzes the reasons why food insecurity in Spain must increasingly be understood as lack of access to sufficient food resources to guarantee the survival and wellbeing of part of the population. Using data collected in an ongoing research project, two possible causes for this are explored. First, it is argued that certain positive developments that seemed firmly established, such as recognition of the right to an adequate diet and the leveling out of social differences in food consumption, are now being reversed by the current economic crisis. Second, the analysis focuses on strategies people in precarious circumstances use to obtain food, their relationship to health, and the need to take social inequality into consideration as an explanatory variable in accounting for different ways of procuring daily sustenance.